Interferon‐gamma serum level and immunohistochemical expression of CD8 cells in tissue biopsies in patients with alopecia areata in correlation with trichoscopic findings. Issue 4 (5th July 2020) - Agamia, Naglaa; Apalla, Zoe; El Achy, Samar; Abdelmaksoud, Eman; Kandil, Noha; Abozeid, Sami
Abstract: Alopecia areata (AA) is an autoimmune form of nonscarring hair loss. The aim of the study was to assess the serum concentration of interferon gamma (IFN‐γ) and CD8 cell expression in lesional skin biopsies in correlation with the disease severity, activity, duration, and trichoscopic findings in patients with AA. The study included 30 patients with AA and 15 age‐ and sex‐matched healthy controls. Trichoscopy was performed and photographs were captured for the alopecic areas, and the enzyme‐linked immunosorbent assay technique was used for serum level of IFN‐γ assessment and immunohistochemistry for CD8 cells. The results obtained indicate that IFN‐γ serum level in patients was significantly higher than that of control subjects, and significantly correlated with the activity status and the duration of the disease. CD8+ T cells infiltrate intensity significantly correlated with severity. Yellow dots (YDs), vellus hair, black dot, and exclamation marks were the most common trichoscopic findings. The presence of black dots significantly correlated to the disease activity, duration, serum IFN‐γ, and CD8+ infiltrate intensity. The presence of YDs significantly correlated with the mean serum IFN‐γ level. Exclamation marks significantly correlated with the disease activity and the degree of CD8+ infiltrate. In conclusion, trichoscopy could be a reliable indicator of the IFN‐γ serum level and CD8+ T cell infiltrate intensity in AA patient.